EEG background frequency is associated with discharge outcomes in non-ICU hospitalized patients with COVID-19 - Seibert, Kaitlin M.; Lee, Wonhee; Eid, Alexandra; Espinal, Amy E.; Klein, Sara A.; Abumurad, Sumayyah K.; Tao, James X.; Issa, Naoum P. (Frontiers in Neurology, 2022)
Objective: To assess risk factors for encephalopathy in non-ICU hospitalized patients with COVID-19 and the effect of encephalopathy on short-term outcomes. Methods: We collected clinical and electrophysiological characteristics of fifty patients with COVID-19 infection admitted to a ward service and who had an electroencephalogram (EEG) performed. Predictors of short-term outcomes including hospital length of stay and discharge disposition, were determined from univariate and multivariate statistical analysis. Results: Clinical delirium predicted encephalopathy on EEG, cefepime use was associated with increased length of stay, and of all factors analyzed, background frequency on EEG alone was correlated with discharge disposition. Conclusion: Encephalopathy is one of the major determinants of short-term outcomes in hospitalized non-ICU patients with COVID-19.